a) [tex]6^{9} *6^{8} =6^{17}[/tex]
dodajesz se 9+8
b)[tex]9^{15}[/tex]
dodajesz 9+1+5 =15
c)(1 i 1/4) [tex]^{9}[/tex]
odejmujesz 10-1 =9
3.
a) 8 to inaczej [tex]2^{3}[/tex]
[tex]2^{3}[/tex] * [tex]2^{3}[/tex] * [tex]2^{5}[/tex] = [tex]2^{14}[/tex]
dodajesz 3+3+5= 14
b)81 to inaczej =[tex]3^{3}[/tex]
[tex]3^{3}[/tex]* [tex]3^{5}[/tex] *[tex]3^{3}[/tex] =[tex]3^{5}[/tex]
dodajesz 3+5-3 =5
c) 64 to inaczej =[tex]2^{6}[/tex] a 16 =[tex]2^{3}[/tex]
[tex]2^{6}[/tex] * [tex]2^{6}[/tex] : [tex]2^{6}[/tex] =[tex]2^{3}[/tex]
6+3-6 =3